The Influence of The Teachers' Reading Habit On Their Teaching Practice: A Narrative Inquiry - Etri Wijayanti; Yan Mujiyanto; Hendi Pratama (English Education Journal, 2022)
We consider the substantial relationship between teachers' reading habits and teaching practices in the Indonesian context. This issue has piqued the interest of research. Therefore, this study investigates how teachers' reading habits influence their teaching practice. This study employs narrative inquiry by Clandinin and Connelly (2000) as a qualitative research design, allowing us to collect rich data through the unique stories of the participants. This study involves three Indonesian English teachers at one of the vocational high schools in Indonesia, namely SMK Negeri 1 Pringapus. Specifically, this study uses a narrative inquiry framework by Clandinin and Conelly (2002). We collected the data through observation, questionnaires, interviews Creswell (2012); transcribing, and coding based on Bailey (2008). Additionally, to obtain trustworthiness, we use the theory of Guba and Lincoln (1982). The findings show that teachers' reading habits have vital roles in their teaching practice. The findings also clearly demonstrate a solid and lasting relationship between teachers' reading habits and teaching practice. This study suggests that educators, in particular, should improve reading habits both for professional needs as teachers and personal needs. It is also necessary to continue to improve the quality of teaching practice by strengthening reading habits. Key Words: teachers' reading habit, narrative inquiry, teaching practice